Pengaruh Orientasi Kewirausahaan dan Inovasi Produk Terhadap Kinerja Usaha UMKM Kuliner di Kecamatan Singaparna Kabupaten Tasikmalaya - Ifqi Hasan Hudori Beq; Aditia Abdurachman (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2026)
This study examines how entrepreneurial orientation and product innovation contribute to the business performance of culinary micro, small, and medium enterprises (MSMEs) in Singaparna District, Tasikmalaya Regency. A quantitative approach with a survey design was employed. From a registered population of 200 active culinary MSME units, a total of 67 respondents were selected using the Slovin formula through simple random sampling. Data collection relied on a structured Likert-scale questionnaire with a response range of 1 to 5. The analytical pipeline involved ordinal-to-interval data transformation via the Method of Successive Intervals (MSI), followed by classical assumption diagnostics and multiple linear regression estimation. Empirical findings confirm that entrepreneurial orientation exerts a positive and statistically significant partial effect on business performance; product innovation likewise demonstrates a positive and significant partial influence. Taken in combination, the two independentt variables explain a substantial portion of the variance in business performance, with product innovation recording a higher regression coefficient and thus emerging as the stronger predictor. These findings carry strategic implications, underlining that sustained product innovation is a critical competitive lever for culinary MSMEs operating in semi-urban market settings.